Mechanical and Physicochemical Characterization of Wood Materials Produced from Larix decidua and Pinus sylvestris L. Tree Species - Yazıcı, Hikmet; Onat, Saadettin Murat (North Carolina State Univ Dept Wood & Paper Sci, 2026)
This study focused on mechanical and physicochemical characterization of wood materials produced from Larix decidua and P. sylvestris L. species. Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR) and scanning electron microscopy (SEM) analyses were employed to examine the structure, chemical bonding, and surface morphology. Mechanical properties, such as tensile strength and elasticity, were evaluated to assess durability and potential applications. The results revealed considerable differences in the chemical composition and mechanical properties of the two species, underscoring their distinct suitability for specific industrial applications. L. decidua exhibited superior mechanical performance compared to P. sylvestris L., with higher bending strength (90.5 N/mm2), compressive strength parallel to the grain (42.1 N/mm2), and density (0.62 g/cm3). Moreover, L. decidua showed greater resistance to decay under outdoor weather conditions compared to P. sylvestris L. These findings provide valuable insights into the potential uses of these wood species in construction, furniture production, and other industries requiring durable and versatile natural materials.
Keywords: Larix decidua; Pinus sylvestris L.; Wood; Mechanical property; FTIR-ATR; SEM